Translation and measurement properties of pregnancy and childbirth questionnaire in Iranian postpartum women - Somayeh Abdolalipour; Shamsi Abbasalizadeh; Sakineh Mohammad-Al; Fatemeh Abbasalizadeh; Shayesteh Jahanfar; Mohammad Asghari Jafarabadi; Kosar Abdollahi; Mojgan Mirghafourvadsnd (BMC, 2024)
Abstract Background Perceived care quality and patient satisfaction have been important care quality indicators in recent decades, and healthcare professionals have been influential on women's childbirth experience. This study investigated the measurement properties of the Persian version of the Pregnancy and Childbirth Questionnaire (PCQ), designed to measure mothers' satisfaction with the quality of healthcare services provided during pregnancy and childbirth. Methods This is a cross-sectional methodological study. Instrument translation, face validity, content validity, structural validity, and reliability evaluation were performed to determine the measurement properties of the PCQ's Persian version. A backward-forward approach was employed for the translation process. Impact scores were selected based on the items' importance to measure face validity. Content validity index (CVI) and content validity ratio (CVR) were calculated to measure content validity, and exploratory and confirmatory factor analyses were used to measure structural validity. The cluster random sampling method was used, resulting in a sample of 250 eligible women referred to the health centers of Tabriz, Iran, who were 4 to 6 weeks after giving birth. Cronbach's alpha coefficient and Intraclass Correlation Coefficient (ICC) using a test-retest approach were used to determine the questionnaire's reliability. Results The impact scores of all items were above 1.5, which indicates a suitable face validity. The content validity was also favorable (CVR = 0.95, CVI = 0.90). Exploratory factor analysis on 25 items led to the removal of item 2 due to a factor loading of less than 0.3 and the extraction of three factors explaining 65.07% of the variances. The results of the sample adequacy size were significant (< 0.001, and Kaiser-Meyer-Olkin = 0.886). The model's validity was confirmed based on the confirmatory factor analysis fit indicators (i.e., RMSEA = 0.08, SRMR = 0.09, TLI = 0.91, CFI = 0.93, x2/df = 4.65). The tool's reliability was also confirmed (Cronbach's alpha = 0.88, and ICC (95% CI) = 0.93 (0.88 to 0.95)). Conclusion The validity and reliability of the PCQ's Persian version were suitable to measure the extent to which Iranian women are satisfied with the quality of prenatal and intrapartum care.